Microstructured Polymer Optical Fibres - Large, Maryanne; Poladian, Leon; Barton, Geoff; van Eijkelenborg, Martijn A. (Springer US : Imprint: Springer, 2008)
Microstructured Polymer Optical Fibres describes the optical properties of microstructured fibres, how they are made and modelled, and outlines some potential applications. These applications include areas where polymer fibres are already used, such as high-data rate transmission for Fibre-to-the Home or within cars, as well as completely new areas such as the photonic bandgap transmission of "difficult" wavelengths. Emphasising a conceptual understanding of the underlying physics, Microstructured Polymer Optical Fibres is clearly written, and includes numerous illustrations. It provides an excellent overview of the latest developments in the field, making them accessible to industry, technical and research audiences.